Applications in human resource management : cases, exercises and skill builders - Nkomo, Stella M., 1947-; Fottler, Myron D.; McAfee, R. Bruce (Cincinnati, OH : South-Western College, 2000)
This book is about: Huaman resource management in perspective; Meeting human resource requirements; Developing effectiveness in Human resources; ...
Keywords: Management; Personnel management -- Case studies; Personnel management -- Problems, exercises, etc